The nucleocapsid protein gene of bovine coronavirus is bicistronic. - Senanayake, S D (1992)
For animal RNA viruses that replicate through an RNA intermediate, reported examples of bicistronic mRNAs with overlapping open reading frames in which one cistron is contained entirely within another have been made only for those with negative-strand or double-stranded genomes. In this report, we demonstrate for the positive-strand bovine coronavirus that an overlapping open reading frame potentially encoding a 23-kDa protein (names the I [for internal open reading frame] protein) and lying entirely within the gene for the 49-kDa nucleocapsid phosphoprotein is expressed during virus replication from a single species of unedited mRNA. The I protein was specifically immunoprecipitated from virus-infected cells with an I-specific antipeptide serum and was shown to be membrane associated. Many features of I protein synthesis conform to the leaky ribosomal scanning model for regulation of translation. This, to our knowledge, is the first example of a bicistronic mRNA for a cytoplasmically replicating, positive-strand animal RNA virus in which one cistron entirely overlaps another.